Forensisk litteratur - Bøndergaard, Johanne Helbo (Passage - Tidsskrift for litteratur og kritik, 2012)
Johanne Helbo Bøndergaard: "Forensisk litteratur" Abstract Johanne Helbo Bøndergaard: “Forensic Literature” This article considers a shift in contemporary culture from an era of testimony to an Era of Forensics. Based on Eyal Weizman’s concept of forensic aesthetics a certain mode in contemporary literature on memory and the past is suggested. Works that include traces of the past in the form of photographs and documentation next to the literary text are considered within this framework and Aleksandar Hemon’s novel The Lazarus Project from 2007 is discussed as a case in point.